Social Practice Participants in the Independent Graduation in the Family Hope Program (PKH) - David Prima Darwin; Azwar; Indraddin (GoAcademica Research & Publishing, 2020)
This study aims to describe the social practice of independent graduation participants in the Family Hope Program (PKH) in Nagari Batu Balang, Harau District, Lima Puluh Kota District. This study uses a descriptive-based qualitative approach with the informants selected using a purposive sampling technique. In collecting data used in-depth interview techniques, involved observation, and documentation studies. The results of this study indicate that habitus plays a role in encouraging PKH participants in independent graduation from persistence in working, having a sense of shame, discipline, frugal, and honest. The forms of capital owned by PKH participants in independent graduation are social capital, economic capital, cultural capital, and symbolic capital. The form of the PKH arena that plays PKH participants in independent graduation is to hold monthly meetings to add insight, monthly meetings as a first step to starting a household business, conducting health checks at the Polindes and Puskesmas, paying attention to the presence of children at school, saving to open a household business, dare to open a household business, and use the land around the neighbourhood to grow vegetables and medicinal plants.